Natural golf - Ballesteros, Severiano (Stanley Paul, 1988)
Multi-winner Ballesteros is a golfer of courage and genius. He is a two times US Masters and three times British Open winner. Bill Elliot has been following his career and life closely for over 15 years and in this biography explains what has brought him to the pinnacle of success.